Economic benefits of savings groups in rural Mozambique. Issue 12 (4th December 2017) - Brunie, Aurélie; Rutherford, Diana; Keyes, Emily B.; Field, Samuel
Abstract : Purpose: The purpose of this paper is to examine the impact of savings and loan groups (SGs), alone and combined with a rotating labor scheme ( Ajuda Mútua ), on the economic conditions of the rural poor in Nampula province in Mozambique. Design/methodology/approach: Three pairs of districts were randomized into receiving SG, SG and AM, or no intervention. The study used a mixed-methods sequential explanatory design. Data from a longitudinal survey of 1, 276 households were analyzed using difference-in-difference estimation to assess the impact of SGs on income and asset ownership. Thematic analysis of in-depth interviews with 72 program participants explored specific contributions of SGs to economic outcomes. Findings: Survey results show that program participation had a significant, positive impact on income and asset ownership. Qualitative results indicate that SGs allowed households to bridge seasonal food consumption gaps and meet cash needs during crises. Accumulated savings supported asset purchases. Program activities supported agricultural activity, but enterprise development had limited scope. Challenges to economic development included cultural aversion to risk, inadequate agricultural inputs, low market integration, and limited business opportunities. Practical implications: SGs helped reduce vulnerability to stress events. Programs should analyze the wider structural context to foster a positive enabling environment, and combine SGs with relevant enterprise development services for additional benefits. Originality/value: The importance of savings is increasingly acknowledged, but the contributions and limitations of SGs are not fully understood. This paper also highlights the role of structural context, which remains undervalued in the literature.